ONLINE GAME ADDICTION BEHAVIOR: GENDER AND DURATION OF PLAYING ONLINE GAMES IN ADOLESCENTS - Sari, Novita; Maulidya, Rizki; Afriani, Afriani (Psikoislamedia: Jurnal Psikologi, 2023)
Adolescents advantage online games as an escape from the problems they have in the real life. The various types of online games make adolescents feel challenged so that thet spend a long time playing online games. This online game phenomenon that occurs in adolescents causes online game addiction behaviour. Men are much more likely to play online game so they tend to have higher rates of online game addiction behaviour than do women. This study aims to reveal the sex differences and duration of playing online game affect online game addiction behaviour. This study used a quantitative approach through purposive sampling with a total sample size of 336 adolescents. The research data were analyzed using Linear Regression Analysis. The result showed that sex differences and duration of playing game online affect to online game addiction behaviour.